Political and Economic Situation in Madagascar in the Period of the Forthcoming Presidential Elections in 2018 - K. Safronov (Международная аналитика)
In the run-up of the forthcoming presidential election scheduled for the end of 2018 the political situation in the Republic of Madagascar is worsening. The incumbent president Hery Rajaonarimampianina is being accused of possessing levers of influence on judiciary. However, in the author’s opinion, most of the citizens support the president, and the prospects of political development to a significant degree are dependent on the present socioeconomic situation on the island. Risks of mass protests are quite low. The paper acknowledges the effectiveness of economic policy pursued by the executive power. The current financial situation, as a whole, meets expectations, and the positive results of a budget execution are obvious.